Evaluasi Kritis Terhadap Peran Bhabinkamtibmas Dalam Mengatasi Penyalahgunaan Narkoba Di Kalangan Remaja - Chardelia Penggalih; Cinta Perindu; Shella Amalia Khakim (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The issue of drug abuse among adolescents has become a significant concern worldwide. This study aims to explore the application of police psychology theories in understanding and addressing the behavior of drug use among adolescents. Through a comprehensive literature review, various psychological theories and approaches are examined to provide insights into the underlying factors contributing to drug use behavior in adolescents. The study analyzes the role of psychological factors, such as personality traits, emotional and cognitive processes, social influences, and environmental factors, in shaping drug use behavior. Additionally, the study discusses the implications of these theories for law enforcement strategies, prevention programs, and rehabilitation efforts targeting adolescent drug users. By integrating psychological perspectives with policing practices, this research aims to contribute to the development of more effective and evidence-based approaches in combating drug abuse among adolescents.